Teaching child and adolescent psychiatry to undergraduate medical students - A survey in German-speaking countries - Frank Florian; Frank Reiner (BMC, 2010)
Abstract Objective To conduct a survey about teaching child and adolescent psychiatry to undergraduate medical students in German-speaking countries. Methods A questionnaire was sent to the 33 academic departments of child and adolescent psychiatry in Germany, Austria, and the German-speaking part of Switzerland. Results All departments responded. For teaching knowledge, the methods most commonly reported were lectures and case presentations. The most important skills to be taught were thought to be how to assess psychopathology in children and how to assess families. For elective courses, the departments reported using a wide range of teaching methods, many with active involvement of the students. An average of 34 hours per semester is currently allocated by the departments for teaching child and adolescent psychiatry to medical students. Required courses are often taught in cooperation with adult psychiatry and pediatrics. Achievement of educational objectives is usually assessed with written exams or multiple-choice tests. Only a minority of the departments test the achievement of skills. Conclusions Two ways of improving education in child and adolescent psychiatry are the introduction of elective courses for students interested in the field and participation of child and adolescent psychiatrists in required courses and in longitudinal courses so as to reach all students. Cooperation within and across medical schools can enable departments of child and adolescent psychiatry, despite limited resources, to become more visible and this specialty to become more attractive to medical students. Compared to the findings in earlier surveys, this survey indicates a trend towards increased involvement of academic departments of child and adolescent psychiatry in training medical students.